Neuroprotective Effect of siRNA Entrapped in Hyaluronic Acid-Coated Lipoplexes by Intravitreal Administration - Marcela Coelho Silva Ribeiro; Marcelo Coutinho de Miranda; Pricila da Silva Cunha; Gracielle Ferreira Andrade; Gustavo de Oliveira Fulgêncio; Dawidson Assis Gomes; Sílvia Ligorio Fialho; Frederico Pittella; Christine Charrueau; Virginie Escriou; Armando Silva-Cunha (MDPI AG, 2021)
Since the possibility of silencing specific genes linked to retinal degeneration has become a reality with the use of small interfering RNAs (siRNAs), this technology has been widely studied to promote the treatment of several ocular diseases. Despite recent advances, the clinical success of gene silencing in the retina is significantly reduced by inherent anatomical and physiological ocular barriers, and new strategies are required to achieve intraocular therapeutic effectiveness. In this study, we developed lipoplexes, prepared with sodium alginate as an adjuvant and strategically coated with hyaluronic acid (HA-LIP), and investigated the potential neuroprotective effect of these systems in a retinal light damage model. Successful functionalization of the lipoplexes with hyaluronic acid was indicated in the dynamic light scattering and transmission electron microscopy results. Moreover, these HA-LIP nanoparticles were able to protect and deliver siRNA molecules targeting caspase-3 into the retina. After retinal degeneration induced by high light exposure, in vitro and in vivo quantitative reverse transcription-PCR (RT-qPCR) assays demonstrated significant inhibition of caspase-3 expression by HA-LIP. Furthermore, these systems were shown to be safe, as no evidence of retinal toxicity was observed by electroretinography, clinical evaluation or histology.